PENEGAKAN SANKSI PIDANA DALAM UU NO. 24 TAHUN 2011 TENTANG BADAN PENYELENGGARA JAMINAN SOSIAL - Almira Novia Zulaika (Fakultas Hukum Universitas Sriwijaya, 2021)
ABSTRACT The implementation of the national development sector employment is intended to reach their goals and the Indonesian's goals is being just and prosperous according to Pancasila and The Constitution 1945. Social security given by a company to employees or laborer is an obligation that must be adjusted to. Needs Has become, it is nature that man married to bear and his family. A social security management agency, and abbreviated as Social Security Administration Organization, is the body of laws formed to run programs social security. Social Security Administration Organization consisting of health and employment. In social security, protection is the guarantee that participants benefit maintenance and protection given to basic needs for those who have paid their contributions or it paid by the government. Criminal provisions listed in Social Service's Constitution are the criminal law specifically outside of the Penal Code and is a special section sub system of the whole condemnation system. Thus, the condemnation system in special constitution outside of the Penal Code should be integrated in a general rules. But, in the special constitution outside of the Penal Code it can be made special arrangements which deviate or different with the rules stipulated in the Book 1 of the Penal Code. There are two types of criminal sanctions that is in social service's constitution, where criminal sanctions the first is the threat of sanctions for employers who do not register their employees into social service while sanction the second was for agencies that perform the service itself, social service criminal sanctions is the last sanctions imposed upon or can be said is the sanctions after the most severe administrative sanctions so that criminal sanctions are needed in the social service's constitution as lex specialist or rule of law specifically. Keywords : Social Security Administration Organization(BPJS ), the act of bpjs, special crimes, company, employees